Electrodeposited nickel-manganese terephthalic acid metal organic framework for hybrid battery and water splitting - Khan, Muhammad Waqas; Khan, Amir Sohail; Ali, Rana Basit; Waqas, Muhammad; Elahi, Rohma; Sial, Qadeer Akbar; Seo, Hyungtak (Journal of Alloys and Compounds, 2025)
Metal-organic frameworks (MOFs) possessing great potential towards energy storage and conversion applications has led to the intensive investigation of these materials. MOFs are distinguished by their remarkable properties such as customizable pore topologies and abundant redox-active sites. The present investigation showcases the electro-synthesis of flake-like bimetallic nickel-manganese-Terephthalic acid (NiMn-T) MOF nanostructures on nickel foam, an inventive electrode material, in the absence of a binder. Emphasis has been made on the significance of controlling time of electrodeposition to achieve optimum electrochemical performance. The best performing NiMn-T MOF electrode exhibits notable electrochemical characteristics, and therefore integrated as a hybrid supercapacitor's electrode. The fabricated hybrid device delivers decent energy and power density. From the perspective of water splitting characterizations, NiMn-T MOF showed good HER and excellent OER activities along with an exceptional OER stability of 103 % over 10 h demonstrating its capability for its incorporation into practical applications. Hence, this strategy offers a direct and innovative strategy for the advancement of binder-free electrodes in preparation for the energy storage and conversion systems of the next generation.
Keywords: Customizable; Electro-deposited nickel; Electro-synthesis; Energy storage and conversions; Metalorganic frameworks (MOFs); Overpotential; Property; Redox-active sites; Terephthalic acids; Water splitting; HER; MOF; OER; Overpotential; Supercapacitor; Water splitting